Pure strontium-87 isotope in rubidium biotite from the ukrainian shield - Andreev, A.V.; Valter, A.A.; Dikiy, N.P.; Dovbnya, A.N.; Eremenko, G.K.; Lyashko, Yu.V.; Pisansky, A.I.; Storizhko, V.E.; Uvarov, V.L. (Вопросы атомной науки и техники, 2011)
In lithium pegmatites of Shpoljano-Tashlyksky ore area (Kirovograd block of the Ukrainian shield) the biotites enriched with rubidium are distinguished. X-ray and electron-microprobe study of these minerals has shown that they attributed to low ferruginous biotites of structural modification 1M. By nuclear-physics methods the concentration of rubidium, ⁸⁷Rb and ⁸⁷Sr were defined. By X-ray-fluorescent method Sr/Rb-ratio was defined. From these data the cleanliness ⁸⁷Sr s%=⁸⁷Sr/Srtot×100=96⁺⁴₋₆% received. The natural isotopic abundance of ⁸⁷Sr is 7%. Rb/Sr age of the mineral is estimated as 2.14 billion years that will be coordinated with earlier results.